A review of wood-frame low-rise building performance study under hurricane winds. (15th June 2017) - He, J.; Pan, F.; Cai, C.S.
Highlights: Hurricane hazards, public wind pressure databases, and design wind loads are reviewed. The evolution of the low-rise building FE modeling is summarized. The quantification of the building performance is discussed. Areas requiring future studies are identified to fill knowledge gaps. Abstract: The unsatisfying performance of light-frame low-rise buildings under hurricane winds is a long-standing issue. Most past research effort has been made in creating a wind pressure database using advanced testing facilities, studying "cutout" subassemblies (i.e., roof subassemblies/sheathed shear walls) without considering the imparted influences of the whole system, analyzing load transfer mechanisms within full building models in the linear range, and quantifying building performance for the purpose of estimating economic losses. What still remains unclear is the contribution of some key factors, such as the simplified spatial-temporal varying wind loads, the resolution of numerical models, and the building component capacities, with large uncertainties, to the ultimate building performance. This paper aims to review the state-of-the-art research of four related disciplines that may contribute to a rational building performance assessment from an engineering perspective. Hurricane hazards, public wind pressure databases, and design wind loads are reviewed to indicate the importance of parameters other than wind speed to the building performance. The evolution of the low-rise building FE modeling is summarized with an emphasis on the connection modeling as well as their comparisons with experimental measurements. The quantification of the building performance is discussed by using stochastic finite element modeling techniques. At last, areas requiring future studies are identified to fill knowledge gaps.